Partykularne i uniwersalne w literaturach narodowych - Masłowski, Michał (Postscriptum Polonistyczne, 2020)
Opposition between the notion of universalism, created in the age of Enlightenment and the Romantic tradition, which dominates in Central Europe is discussed in the article. Universalism is understood as the process of emancipation of man, but at the same time, in countries ‘between Russia and Germany’ it is also understood as the rule of adherence. In the Romantic tradition there is the symbolic extrapolation of historic experiences and the use of metaphors that have ethical universalism, both of which are described by the author in this article. The understanding of culture as a spiritual sphere which unites the national spirit was destroyed in the 20th century due to totalitarianism, but this grotesque tragedy from our absurd history has created ‘antimodern modernism'.